Hierarchical certificateless authenticated key agreement protocol - Hang SU; Jian-wei LIU; Rui TAO (Tongxin xuebao)
A hierarchical certificateless authenticated key agreement protocol was proposed, and the proposed protocol was proved secure in extended Canetti-Krawczyk (eCK) model, the security of the protocol was based on the computa-tional Diffie-Hellman assumption. In the protocol, a root PKG authenticates the identity and generates a partial private key for lower-level PKG which authenticate the identity and generate a partial private key for users, private key generated by partial private key and user selected secret value. Comparing with the existing protocols, the protocol is efficient without bilinear pairings computation.